Measuring Youth Empowerment: An Illustration Using the Example of Tunisia - Micheline Goedhuys; Michael Grimm; Aline Meysonnat; Eleonora Nillesen; Ann-Kristin Reitmann (Institute of Labor Economics (IZA), 2021)
Youth empowerment, i.e., the ability of young people to take control over key aspects of their lives, has become a growing concern to achieving sustainable development worldwide. An increasing number of policy interventions is targeting the youth, but to monitor the progress a better understanding on what constitutes youth empowerment is needed. However, in contrast to the area of women's empowerment, little progress has been made on determining which domains of empowerment are important for youth and how they can be operationalized with indicators for measurement. We propose four domains of youth empowerment with corresponding indicators and use a well-established methodology for constructing a composite index. Using data from a household survey in Tunisia including a sample of young adults (18 to 30 years old), we assess youth empowerment in the proposed domains, explore correlates to empowerment and assess the link between youth empowerment and youth well-being. The proposed approach can help to monitor youth empowerment in various contexts and to evaluate the effectiveness of youth interventions.
Keywords: C43; D91; D39; J13; 330; youth empowerment; measurement; multidimensional index; well-being; Middle East and North Africa region